2019
DOI: 10.1186/s13068-019-1429-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of lignocellulosic degradation in high-moisture alfalfa via anaerobic bioprocess of engineered Lactococcus lactis with the function of secreting cellulase

Abstract: Background Butyric fermentation and a substantial loss of dry matter (DM) often occur in alfalfa silage during the rainy season, which is not conducive to subsequent biofuel production. Currently, there have been negative effects on the combination of cellulases and lactic acid bacteria (LAB) on processing high-moisture alfalfa silage; however, transgenically engineered LAB strains that secrete cellulase have been proposed as an alternative approach to avoid the above problem. The objective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Fermentation highly depends on the presence of natural microbiota, the chemical composition of the forage crops, mainly WSC, and the presence of nitrogenous components [ 51 ]. Recently, Liu et al (2019) [ 52 ] studied alfalfa silage and reported that LAB-inoculated silage has distinct shapes, colors, smells, and textures after 60 days of fermentation. The control silage (without inoculum) produced an unpleasant odor and seemed black and sticky.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation highly depends on the presence of natural microbiota, the chemical composition of the forage crops, mainly WSC, and the presence of nitrogenous components [ 51 ]. Recently, Liu et al (2019) [ 52 ] studied alfalfa silage and reported that LAB-inoculated silage has distinct shapes, colors, smells, and textures after 60 days of fermentation. The control silage (without inoculum) produced an unpleasant odor and seemed black and sticky.…”
Section: Discussionmentioning
confidence: 99%
“…The engineered strains of MG1363 containing bgl1, cbh2, and egl3 gene of T. reesei were constructed in our lab by Liu et al (2019). After culturing in GM17 broth medium at 30°C for 30 h, engineered strains containing bgl1, cbh2, and egl3 gene were mixed at 1:1:1, 2:1:1, 1:2:1, 1:1:2, 1:1:0, 1:0:1, and 0:1:1 and were named HT2, HT3, HT4, HT5, E1C1, E1B1, and C1B1 separately.…”
Section: Lab Strains Material and Ensiling Treatmentsmentioning
confidence: 99%
“…According to the method reported by Liu et al (2019), the LAB, aerobic bacteria, and clostridia in alfalfa materials were counted after harvesting from the eld for 2 h. The BC of alfalfa materials was measured by the method reported by Liu et al (2018). The DM, NDF, ADF, ADL, and WSC in alfalfa materials were measured by the same method reported by Li et al (2019).…”
Section: Microbial and Chemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations